Therapeutic potential of chemically modified siRNA: Recent trends. (16th May 2017) - Selvam, Chelliah; Mutisya, Daniel; Prakash, Sandhya; Ranganna, Kasturi; Thilagavathi, Ramasamy
Abstract : Small interfering RNAs (siRNAs) are one of the valuable tools to investigate the functions of genes and are also used for gene silencing. It has a wide scope in drug discovery through in vivo target validation. siRNA therapeutics are not optimal drug‐like molecules due to poor bioavailability and immunogenic and off‐target effects. To overcome the challenges associated with siRNA therapeutics, identification of appropriate chemical modifications that improves the stability, specificity and potency of siRNA is essential. This review focuses on the various chemical modifications and their implications in siRNA therapy. Abstract : Ribose Modifications, Phosphate Backbone Modifications, Nucleobase Modifications, Modification to the Termini and Conjugate groups, siRNA Binding.